2020
DOI: 10.1021/acs.nanolett.0c00422
|View full text |Cite
|
Sign up to set email alerts
|

Soft Plasmonic Assemblies Exhibiting Unnaturally High Refractive Index

Abstract: The increases in refractive indices (n) of materials are crucial for transformative optical technologies. With the progress of monolithic lithography, large advances have been achieved with several semiconductors, including silicon, germanium, and gallium arsenide, which generally provide higher n of ∼4.0 compared to those of other elements. Nevertheless, above this upper limit of naturally available n, the range of light–matter interactions could be unprecedentedly expanded, which in turn enriches the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…[51][52][53][54] The variously shaped metallic colloids acting as electric meta-atoms can be closely packed into a large-area 2D or 3D superlattice using currently available self-assembly technologies such as convective selfassembly, depletion forcing, DNA self-assembly, and interfacial assembly (e.g., Langmuir-Blodgett (L-B)). [55][56][57][58][59][60][61]72,[134][135][136][137][138][139][140] In these [51] b) In 2009, Fan and co-workers [18] theoretically suggested that the elaboration of the shape of conductive meta-atoms from a cube to a 3D "I"-beam frame can dramatically suppress the diamagnetism (M) and the modulation of permeability (μ eff ), while the facet interfaces between meta-atoms can boost the capacitive coupling between the induced EDs and resultant polarization (P)/ε eff . c) In 2011, Min and co-workers [19] found that a 3D "I"-beam frame design can be transformed into its 2D counterpart, which can facilitate the experimental realization.…”
Section: Progress On Colloidal Optical Metamaterials Exhibiting Unnatmentioning
confidence: 99%
See 4 more Smart Citations
“…[51][52][53][54] The variously shaped metallic colloids acting as electric meta-atoms can be closely packed into a large-area 2D or 3D superlattice using currently available self-assembly technologies such as convective selfassembly, depletion forcing, DNA self-assembly, and interfacial assembly (e.g., Langmuir-Blodgett (L-B)). [55][56][57][58][59][60][61]72,[134][135][136][137][138][139][140] In these [51] b) In 2009, Fan and co-workers [18] theoretically suggested that the elaboration of the shape of conductive meta-atoms from a cube to a 3D "I"-beam frame can dramatically suppress the diamagnetism (M) and the modulation of permeability (μ eff ), while the facet interfaces between meta-atoms can boost the capacitive coupling between the induced EDs and resultant polarization (P)/ε eff . c) In 2011, Min and co-workers [19] found that a 3D "I"-beam frame design can be transformed into its 2D counterpart, which can facilitate the experimental realization.…”
Section: Progress On Colloidal Optical Metamaterials Exhibiting Unnatmentioning
confidence: 99%
“…In this context, the self-assembly-enabled packing of a metallic colloidal superlattice can provide an effective platform for achieving unnaturally high n eff at optical frequencies. [55][56][57][58][59][60][61] Herein, we explore the unnaturally achievable high refractive indices by packing metallic colloids into a 2D superlattice, as summarized in Figures 3 and 4. Toward this, we used the method of s-parameter retrieval, as briefly introduced in Section 2.2.…”
Section: Progress On Colloidal Optical Metamaterials Exhibiting Unnatmentioning
confidence: 99%
See 3 more Smart Citations